2018
DOI: 10.4202/app.00472.2018
|View full text |Cite
|
Sign up to set email alerts
|

A serpulid-Anodontia-dominated methane-seep deposit from the upper Miocene of northern Italy

Abstract: A limestone deposit with an unusual fauna is reported from the late Miocene of northern Italy (Ca' Fornace site). The petrography of the carbonate and its distinct Naturali, 51, Via Medaglie D'Oro 51, 48018 Faenza, Italy. Marco Taviani [marco.taviani@bo.ismar.cnr.it], Institute of Marine Sciences, Italian National Research Council, Via Gobetti 101, 40129 Bologna, Italy; Biology Department, Woods Hole Oceanographic Institution, 266 Woods Hole Rd, Woods Hole, MA 02543, USA; and Stazione Zoologica Anton Dohrn,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 44 publications
1
4
0
Order By: Relevance
“…Although occurrence data of "Keratosa"-type sponge fossils or similar structures are accumulating [4], not all of them were illustrated with enough information or proper preservation as required to evaluate using criteria I-VI (e.g., [18,70]). However, examples conforming criteria I-V are indeed known throughout the whole Phanerozoic (e.g., Cambrian [5]; Ordovician [71]; Devonian [2]; Carboniferous [6]; Triassic, this study; Miocene [72]). In some of these examples ( [5,6] and this study), characteristic VI is also present.…”
Section: "Keratosa"-type Demosponge In the Fossil Record: Known And U...supporting
confidence: 57%
“…Although occurrence data of "Keratosa"-type sponge fossils or similar structures are accumulating [4], not all of them were illustrated with enough information or proper preservation as required to evaluate using criteria I-VI (e.g., [18,70]). However, examples conforming criteria I-V are indeed known throughout the whole Phanerozoic (e.g., Cambrian [5]; Ordovician [71]; Devonian [2]; Carboniferous [6]; Triassic, this study; Miocene [72]). In some of these examples ( [5,6] and this study), characteristic VI is also present.…”
Section: "Keratosa"-type Demosponge In the Fossil Record: Known And U...supporting
confidence: 57%
“…Mass occurrences of serpulids in ancient methane seep deposits, known as "fossil serpulid seeps," have perplexed scientists for decades, and the recognition of paleoseep indicator species continues to be of value for geologists and geobiologists alike. For serpulids, which permanently inhabit calcareous tubes, seven taxa (including Laminatubus) have been reported from early Cretaceous to Miocene seep communities ~150 to 200 million years ago (15)(16)(17). They appear attached to, or in layers immediately adjacent to, known chemosynthetic vesicomyid clams, lucinid clams, or bathymodiolin mussels, prompting the suggestion that serpulids found in fossil seep deposits were actually regular members of the chemosynthetic community, as opposed to arriving only after seepage had ceased (15).…”
Section: Introductionmentioning
confidence: 99%
“…Based on these evidence, they can be interpreted as the product environments by a consortium of methanotrophic archea and sulphate-reducing bacteria (Boetius et al, 2000) as confirmed by the presence of large bivalves belonging to Mytilidae, Lucinidae and Vesicomyidae. The high productivity of cold seeps provides habitats for other organisms that do not possess bacterial symbionts, like serpulid tubeworms (Kiel et al, 2018), that occur mainly up in the section.…”
Section: Discussionmentioning
confidence: 99%